Energia escura e formação de estruturas em larga escala - Liberato, L [UNESP] (2007)
We investigate large scale structure formation in universe with dark energy presence. The dark energy influence on cosmological perturbation growth is exerted both through its effect on the expansion rate of background, and through its own density fluctuation as well. To compute the rate of formation of massive objects we employed the spherical collapse formalism, which was generalized to include fluids with pressure. An important effect caused by fluctuations in dark energy associated with dark matter halos is the induction of dark energy halos damping the growth of structures when the equations of state are non-phantom; on the other hand, phantom models generate dark energy voids, enhancing the growth of matter halos. Other important effect occurs when we consider the possibility of dark energy changing its equation of state when there are large differences between densities in the background and in the halos. The large number of dark energy parametrizations obtained with supernova Ia data are only sensitive to redshifts up to order one. We show these parametrizations produce distinguishable signatures in cluster formation using the Press-Schechter formalism. Therefore, future observations of galaxy clusters can provide important constraints on the behavior of dark energy in the course of universe evolution